THE IMPROVED CONTECT OF THE SECTION, PHYSICS OF ELEMENTARY PARTICLES AT THE BACHELOR DEGREE OF HIGHER EDUCATION - Davletniyazov Salamat Paluaniyazovich; Eshbaeva Malika Maxsetbaevna (Galaxy International Interdisciplinary Research Journal, 2021)
This article is about the development of an improved content of the section " Physics of Elementary Particles " at the becholor degree of higher education, thereby increasing the effectiveness of teaching.